OVERVIEW OFENVIRONMENT & ENERGY FOR SUSTAINABLE CONSTRUCTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The per capita income of an individual decides the growth rate of any country. In the light of fact that the construction industries plays vital role in growth of country with development of infrastructure, it has the responsibility to provide sustainable infrastructure. The infrastructure is rapidly developing in the countries like India still there is huge scope for improvement. Authors have tried spreading the light over various consequences related to the recent practices in construction industries by considering the various areas of improvement. The global resources have been extensively used by the construction process to meet the demand in the targeted time. It’s the need of time to consider and promote various ways to reduce the pollution occurring during the construction and building functions. This paper justified the requirement of sustainable construction options available and proposed by various researchers during the recent times.